(untitled) (Interdisciplinary Studies Journal, 2024)
This article discusses and addresses the relevance of full-time education, focusing on the study of the Program for Reinforcement and Optimization of Regular Education, known as PROEDUCAR, in the municipality of São Mateus do Maranhão. The main objective of this research is to understand the impact of programs aimed at extending the school day, specifically the PROEDUCAR program, on students’ academic performance, social and emotional development, and the overall school dynamic. The study was conducted using a qualitative methodology, including literature reviews, interviews, and direct observation of the program’s activities. This allowed for highlighting the importance of full-time education programs and their impacts on students’ reality. The present study begins with some initial considerations. Second, a brief introduction to full-time education is presented. Third, the data collected during the research is presented. The fourth part is dedicated to a grounded discussion and debate on the data collected. Finally, the study concludes with the final considerations.